COMPARATIVE STUDY BETWEEN INTRALESIONAL INJECTION OF PLATELET RICH PLASMA AND INTRA LESIONAL TRIAMCINOLONE FOR THE TREATMENT OF ALOPECIA AREATA - Afsar khan, Faheema; Majid Hussain,; Bushra Muzaffar Khan,; Saima Afsar,; Mairah Shafique,; Sami ul Haq,; Nadia Akbar,; Adeel Siddique, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Alopecia areata is an autoimmune disorder of patchy non scarring hair loss. Steroids, either Intralesional, e.g, triamcinolone or potent topical, e.g, clobetasol are the first line treatment. Platelet rich plasma is an autologous concentrated plasma with growth factors which enhances regeneration of hair follicles. It is simple and effective treatment with no major side effects. Objective was to compare the efficacy of intralesional injection of platelet rich plasma and triamcinolone in patients of alopecia areata. It was a randomized controlled trial (open-labelled), conducted at the Dermatology Department, Combined Military Hospital Abbottabad from 1st May to 31st December 2021. Methods: Sixty clinically diagnosed patients of alopecia areata of the scalp were enrolled in the study. They were divided into two groups, A and B. Random numbers table was used to allocate 30 patients into each group. Group A patients were given an intralesional injection of triamcinolone while intralesional platelet rich plasma was given to Group B. Both treatments were repeated at one-month intervals for four months. In the study, Chi-square tests were used to compare effectiveness. It was considered significant when the p-value turned out to be <0.05. Results: There was significant difference in complete response rate between intralesional injection of steroid and intralesional injection of platelet rich plasma. Platelet rich plasma was less effective (p =0.05). Local corticosteroid injection was significantly more effective than platelet rich plasma (p <0.05). Conclusion: Intralesional injection of steroid is an effective and considerable treatment for alopecia areata. This study also proposes intralesional injection of platelet rich plasma as an alternative therapy for alopecia areata as it is not associated with serious local side effects.